Everyday Ethnicity in Sri Lanka: Up-Country Tamil Identity Politics - Bass, Daniel (Routledge contemporary South Asia series, 2013)
Focusing on notions of diaspora, identity and agency, this book examines ethnicity in war-torn Sri Lanka. It highlights the historical development and negotiation of a new identification of Up-country Tamil amidst Sri Lanka's violent ethnic politics. Over the past thirty years, Up-country (Indian) Tamils generally have tried to secure their vision of living within a multi-ethnic Sri Lanka, not within Tamil Eelam, the separatist dream that ended with the civil war in 2009. Exploring Sri Lanka within the deep history of colonial-era South Asian plantation diasporas, the book arg
Keywords: 1978-; Ethnic identity; Malaiyaha Tamil (Sri Lankan people); Government policy; Malaiyaha Tamil (Sri Lankan people); Political aspects; Sri Lanka; Politics and government; Politics and government; Sri Lanka; Race relations; Sri Lanka; Tamil diaspora; Malaiyaha Tamil (Sri Lankan people); dept.ant; faculty_collection

Stone Tool Variability and the Ecological Context of the Earliest Archaeological Record - Rogers, Michael J. (2013)
Keywords: dept.ant; faculty_collection; sabbatical_report

Violence and warfare in the prehistoric San Francisco Bay area: Regional and temporal variations in conflict - Bartelink, E.J.; Andrushko, V.A.; Bellifemine, V.I.; Nechayev, I.; Jurmain, R. (The Routledge Handbook of the Bioarchaeology of Human Conflict, 2013)
The study of the origin and causes of interpersonal violence and warfare in human prehistory has drawn the interest of anthropologists for over a century (Ember and Ember 1995; Ferguson 1984; Ferguson and Whitehead 1992; Gat 2000; Haas 1990; Keeley 1996; Kelly 2000; Lambert 2002; McCall and Shields 2008; Martin and Frayer 1997; Otterbein 1994; Turney-High 1971; Walker 2001; Wrangham and Peterson 1996). Over the past few decades, a plethora of research has provided unambiguous evidence for interpersonal violence and warfare in a vast number of prehistoric societies, countering the notion of a “pacified past” (Keeley 1996; Lambert 2002; Maschner and Reedy-Maschner 1998; Milner 1995; Walker 2001). This is particularly true in California, where the notion of idyllic, peaceful hunter-gatherer groups living in a bountiful temperate climate has been contradicted by numerous skeletal studies revealing evidence of cranial trauma, projectile point injuries and trophy-taking (e.g. Andrushko et al. 2005, 2010; Jurmain 1991, 2001; Jurmain and Bellifemine 1997; Jurmain et al. 2009; Lambert 1994, 1997; Nelson 1997; Walker 1989; Wiberg 2002). The study of human skeletal remains provides a unique perspective on trauma in pastsocieties that complements evidence from material culture, site context and ethnographic and ethnohistoric accounts (Jurmain 1999; Larsen 1997; Walker 1997). While early trauma analyses focused on single case studies or small samples, more recent studies have followed a population-based perspective, with greater emphasis on the examination of trauma patterns in larger and more representative skeletal samples (e.g., Lambert 1994, 1997; Lovejoy and Heiple 1981; Steadman 2008). This population-based perspective has allowed osteologists to recognize individual, temporal and geographic variation in traumatic injuries due to a wide range of cultural, biological and environmental factors. Over the past two decades, several studies have also increasingly focused on more definitiveindicators of violence, such as cranio-facial trauma and injuries associated with embedded projectile points or other types of weaponry (e.g. Andrushko and Torres 2011; Buzon and Richman 2007; Dawson et al. 2003; Fiorato et al. 2000; Jurmain et al. 2009; Kanz andGrossschmidt 2006; Lambert 1994, 1997; Lessa and Mendonça de Souza 2004, 2006; Murphy et al. 2010; Owens 2007; Paine et al. 2007; Smith, 1996, 1997, 2003; Standen and Arriaza 2000; Steadman 2008; Torres-Rouff and Costa Junqueira 2006; Tung 2007; Walker 1989, 1997; Webb 1995; Willey and Emerson 1993). Peri-mortem mutilation, including evidence of dismemberment and trophy-taking (e.g. scalping, body part removal), is also considered a corollary to interpersonal violence and warfare practices (Andrushko et al. 2005, 2010; Lambert 2007; Steadman 2008; Tung 2007, 2008; Tung and Knudson 2008; Verano 2003). When analysed together, these direct indicators of violence – cranio-facial trauma, projectile point injury and evidence of trophy-taking – provide powerful evidence for interpersonal violence in a society. Moreover, when these indicators of conflict are analysed from a population-based perspective, as described above and employed in the present study, a more accurate and nuanced understanding of violent conflict in the past can be achieved. © 2014 Christopher Knüsel and Martin J. Smith for selection and editorial matter; individual contributions, the contributors. All rights reserved.
Keywords: dept.ant

Political economy and language: A review of some recent literature - McGill, Kenneth (Journal of Linguistic Anthropology, 2013)
Keywords: dept.ant

The African Acheulean - Sahnouni, Mohamed; Semaw, Sileshi; Rogers, Michael (The Oxford Handbook of African Archaeology, 2013)
This article argues that the Acheulean is perhaps the longest lasting cultural–technological tradition in human history, dating from around 1.7 to 0.3 Mya and roughly corresponding to the time during which H. Erectus and H. Heidelbergensis lived in Africa. Unlike earlier Oldowan technology, Acheulean cores — handaxes, cleavers, and picks — were standardised, of predetermined shape and made on large cobbles and flakes. The extensive Acheulean archaeological record throughout Africa over 1.4 million years described is testimony to the success of this technology’s makers in different habitats, altitudes, and settings, but also to its apparent conservative cultural nature: a learned tradition passed on through thousands of generations of highly mobile hominin groups with small population sizes. Although there are differences between Early and Late Acheulean technology, the makers of these tools may have undergone more significant changes with respect to the use of other technologies, strategic land use, and social life.
Keywords: dept.ant

Discourse, organization, and the welfare state in the former east berlin - McGill, Kenneth (PoLAR: Political and Legal Anthropology Review, 2013)
In this article, I examine the statements and actions of two key informants, both of whom direct welfare programs in a district of the former East Berlin. I argue that this evidence points to a particular modality of political rationalization, which I dub organizational discourse. The entanglement of organizational discourse and governmentality are explored, as is the place of organizational discourse within both the liberal welfare state and the bygone state socialist regime.
Keywords: Discourse; Germany; Organization; Power; Welfare state; dept.ant

No magic tricks: commodity, empowerment, and the sale of StreetWise in chicago - McGill, Kenneth (Journal of Linguistic Anthropology, 2013)
Use-value and exchange-value are pragmatic features of commodity exchange which are apparent from the careful study of specific interactions, as well as from the viewpoint of economic processes at large. While Marx's well-known attempt to describe this pair of concepts in Capital (2001) takes the latter tack, I attempt here to take the formeri.e., to approach the composition of the commodity from the point of view of the pragmatics of interaction. In doing so, I offer a semiotic model of the valuation of commodities which differs from accounts given by Kockelman (2006) and Agha (2011). The ethnographic object at stake in this essay is StreetWise, a Chicago street newspaper said to have empowering effects on its vendors.
Keywords: Commodity; Empowerment; Street newspapers; United States; Value; dept.ant